Potensi Hasil Jarak Pagar (Jatropha curcas L.) pada Satu Tahun Budidaya di Lahan Kering Lombok Barat, Nusa Tenggara Barat - Bambang B. Santoso; , Hasnam; , Hariyadi3; Slamet Susanto; Bambang S. Purwoko (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2008)
Productivity of Physic Nut (Jatropha curcas L.) depends on environment and culture intensity. We evaluated yield potential of Jatropha curcas L. at dry land (sandy entisol soil type) of West Lombok, West Nusa Tenggara using three types of propagules, i.e., stem cutting, seed, and seed after pruning and were designed with Randomized Block Design in three replications during November 2006 until November 2007. Result showed that productivity of nut is 880.78 kg/ha (352.31 g/plant) from stem cutting, 749.81 kg/ha (299.92 g/plant) from seed, and 484.11 kg/ha (193.64 g/plant) from seed followed by pruning after 2 weeks planting.